THE IMPACT OF THE WORK-LIFE BALANCE ON WORK ENGAGEMENT OF NON-ACADEMIC EMPLOYEE IN HIGHER LEARNING INSTITUTIONS IN MALAYSIA - Shafie b. Hj. Aliasah, Mohammadd Wazir; Abdullah, Zuraidah; Shafee, Salwati (Universitas Pendidikan Indonesia, 2023)
Work Life Balance is an important aspect in the lives of individual employee. It is highly associated with their ability to perform well at work and live a happy and contented life. Work life balance affects every aspects of individual either emotionally or psychologically. This study looks at the level of work-life balance as well as the work involvement of non-academic employees of higher learning institutions in Malaysia. Additionally, it also looks at how the work-life balance affects individual work involvement. Data of this quantitative study were gathered through a set of questionnaire which was administered to 335 non-academic employees of higher learning institutions in Malaysia. Analysis of findings were based on descriptive analysis using SPSS 23 version by looking at the mean and standard deviation. It also looked at the effects of work life balance on work engagement by undertaking pearson correlation analysis. The findings of the study provide and insight on the level of work life balance and work engagement as practiced by the non-academic employees of Malaysian higher learning institutions. The findings also illustrates the significant relationship between work life balance as well as work engagement among non-academic employees in Malaysian higher learning institutions.